Application of the Monte Carlo Method to Pricing Lookback Fixed Option with Stochastic Volatility - Hidayanti, Sri Amalia; Rahmi, Emli; Yahya, Lailany (Gammarise Publishing, 2025)
Options are a derivative product that trades the right to call and put on an asset at a certain price and during an agreed time. Determining the optimal option price is often difficult due to changes in stock prices. One model that can be used to calculate the price of Lookback Fixed options is the Monte Carlo Method with stochastic volatility of the Heston model, with parameter estimation using Ordinary Least Squares (OLS), and Euer-Maruyama and calculation of the effect of initial stock price, strike, and maturity time. The estimated stock price is then used to calculate the Lookback Fixed option price using the Monte Carlo method. The research results obtained good results with a fairly small error rate. In addition, the analysis of the effect of strike price, strike, and maturity time shows results consistent with option pricing theory.